Effects of drop jump training from different heights and weight training on vertical jump and maximum strength performance in female volleyball players - Sotiropoulos, K.; Smilios, I.; Barzouka, K.; Christou, M.; Bogdanis, G.; Douda, H.; Tokmakidis, S. P. (The Journal of Strength and Conditioning Research, 2023)
This study compared the effects of drop jump (DJ) training from different drop heights and weight training on vertical jump and maximum strength performance. Fifty-five female volleyball players (age: 23.8 ± 4.3 years) were randomly and equally allocated to a control group (volleyball training, CG); a volleyball and weight training group (WG); and 3 volleyball, weight, and drop jump training groups. One group performed DJ training from the optimal drop height, i.e., the height that elicited the highest ratio of jump height to contact time (OG), a second group from a drop height 25% higher than the optimal (HG), and a third group from a drop height 25% lower than the optimal (LG). Drop jump and weight training were performed 1-2 times per week, for 8 weeks for a total of 13 sessions. After training, vertical jump performance improved by 3.6-17.4% (p < 0.05; effect size [ES]: 1.03-1.23) in the OG and the HG compared with the LG, WG, and CG (p < 0.05; ES: 0.03-0.58). Drop jump height from drop heights 20-70 cm increased by 10.0-20.2% (p < 0.05; ES: 0.59-1.13) for the OG and the HG, while reactive strength index increased (p < 0.05; ES: 0.74-1.40) by 19.6-33.9% only in the HG compared with the CG. Half-squat maximum strength was increased in all experimental groups by 17.4-19% compared with the CG (p < 0.05) with no differences (p > 0.05) observed among them. The use of the optimal height or a moderately higher drop height by 25% for DJ training, combined with weight training, seems to be the most beneficial option to improve vertical jump and reactive strength index in female volleyball players.